2003
DOI: 10.1093/ps/82.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Recursive prediction of broiler growth response to feed intake by using a time-variant parameter estimation method

Abstract: The objective of this study was to explore whether time-variant parameter estimation procedures allow modeling and predicting the dynamic growth response of broiler chickens to feed intake in real time. A recursive linear model was used that estimated the model parameters every 24 h based on a fixed number of actual and past measurements (i.e., time window). Based on 48 datasets, it was concluded that the mean relative prediction error (MRPE) of the recursive linear modeling approach had a minimum for a window… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…Dietary ME is a key input that controls broiler growth trajectory (Aerts et al, 2003). In addition, mathematical functions of growth in poultry have played a key role in poultry improvement programmes (Nahashon et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary ME is a key input that controls broiler growth trajectory (Aerts et al, 2003). In addition, mathematical functions of growth in poultry have played a key role in poultry improvement programmes (Nahashon et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Growing birds must eat extra feed to provide additional energy for the synthesis of body tissues. On the other hand, dietary energy has been suggested to be the key input that controls broiler growth trajectory (Aerts et al, 2003). Recently, Nahashon et al (2010) demonstrated that dietary protein and energy can affect the growth parameters of the French guinea fowl based on the Gompertz-Laired function.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary CP and ME have been suggested to be the key inputs that control broiler growth trajectory (Aerts et al, 2003). In addition, mathematical models of growth in poultry have played a key role in poultry improvement programs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that feed restriction resulted in alterations of organs and activities of digestive enzymes, confirming a functional adaptation to feed restriction. Aerts et al (2003a) introduced a procedure that modeled and predicted the dynamic growth response of broiler chickens to feed intake in real time. This approach allowed the prediction of broiler growth without any prior knowledge of the system and took into account the time-variant nature of the growth process of each flock of birds.…”
Section: Introductionmentioning
confidence: 99%